Abstract 4143332: Cross-Platform Variations in Transthoracic Echocardiography: Implications for Clinical Decision-Making - Hashemi, Mohammad; Farsiani, Yasaman; Pressman, Gregg; Amini, MohammadReza; Kheradvar, Arash (Circulation (New York, N.Y.), 2024)
Background: Precise measurement of cardiac chamber size and function is crucial for clinical decision making, and these measurements should be consistent across different echocardiography systems. Despite the assumption that modern echocardiography machines have negligible cross-platform variations, few studies have rigorously compared them. This study evaluates the cross-platform variations between Philips EPIQ CVx (release 9.0.3) and Canon Aplio i900 (release 7.0) in assessing cardiac volumes, ventricular function, and valve structures. Hypothesis: Data acquired across various echocardiography platforms exhibit statistical equivalence. Aims: To study cross-platform variations in transthoracic echocardiography and their implications for clinical decision-making Methods: In this gender-balanced prospective study, 40 volunteers aged 40 and older were scanned sequentially by both systems. Each subject was scanned by the same sonographer using identical settings for both 2D and 4D acquisitions. Ventricular volumes were compared using Simpson's biplane method. Data were analyzed by two board-certified cardiologists with respect to diagnostics. Results: Left ventricular end-systolic volume (LVESV) and left ventricular ejection fraction (LVEF) showed no significant differences (p>0.05) between platforms across both 2D and 4D methods. However, left ventricular end-diastolic volume (LVEDV) significantly differed (p<0.03) between platforms. Right ventricular volumes and ejection fraction (RVESV, RVEDV, RVEF) from 4D imaging were consistent across platforms (p>0.05), but 2D versus 4D volume measurements showed significant differences (p<0.01) within each platform. Notable differences between platforms were observed in LV Systolic Dyssynchrony Index (p=0.03), LV Longitudinal Strain (p=0.04), LV Twist (p=0.004), and LV Torsion (p=0.005). cardiologists' assessments of aortic and mitral valve's structure varied between platforms, with a notable increase in frequency of reported valvular abnormalities when using the Philips platform (Fig.1). Conclusions: While LV and RV volumetric measurements are largely consistent across platforms, LV strain metrics show significant variation. Differences in valve structure assessment between platforms suggest that interpretation may vary depending on the echocardiography system used. The study results suggest that patients should undergo follow-up examinations using the same echocardiography platform to ensure diagnostic consistency.